Metaphoricity in the novel Pelagia and Black Monk by Boris Akunin - Molnár, Angelika (Slavica, 2024)
The paper discusses the tropological game in Boris Akunin’s detective novel Pelagia and the Black Monk. The author focuses on the transformation of the main images in this contemporary work. Various periphrases and similes are then studied, as well as the destruction and renewal of redundant tropes, and the generation of new metaphors, particularly those related to color, nature, and zoomorphic images (e.g. the color black, rays). The figurative order of the text of the novel offers such potential correlations that expand the plan of interpretation of the novel in a new and unexpected direction, testifying to a truly postmodern rewriting of lingual, literal, and poetical clichés. A key role in this process is played also by details (see Z. Hajnády).